RELATIONSHIP BETWEEN SITTING POSTURE AND THE USE OF FURNITURE RECOMMENDED BY ISO 5970 IN A SCHOOL POPULATION (Cuestiones de Fisioterapia, 2004)
Foreword: The work's aims are analyzed and value the school furniture dimensions (chairs and tables) used by different ages children population, and compare the results with the Iso Standard's suggestions, and describe the use or not of suggest furniture influence on the seating posture. Material and Method: A randomly children population of Salamanca is chosen. Each student seating posture is observed, while they're pay attention to the teacher and a fill which includes the different parameters that describe the seating posture. Dimensions of the different chairs and tables models are measured, and the results are taken in lists. The height of each subject is measured. Results: Subjects studied are 68 who belong to 3°, 4°, 5° or 6° primary classes. The 51.5% were girls and the rest boys. The average age is 10.38 ±1.244 years and the average height is 144.74 cm. Five different chair models (A, B, C, D, E) have been found and two tables (A and B) that dimensions aren't similar to ISO Standard's suggestions. The 44.11% of the subjects used the chair suggest to it height, however only the 14.7% used a table recommended. A classes homogeneity didn't exist. The subject who didn't use suggested chair tend to: keep an anterior seating posture (50%), adopt a bent position of the spine (68.4%), non-support the foot on the floor (53.3%) and not use the back of the seat (50%). However, these results weren't statistically expressive. Conclusions: The seating posture is in relation to the furniture used. The non suggested furniture used can be the responsible for the incorrect seating posture.